Low-Risk Foot and Ankle Stress Fractures in The Pediatric Population: A Case Series. Issue 5 (31st May 2022) - Gremillion, Matthew; Ghanta, Ramesh; Borici, Neritan; Kushare, Indranil
Background: Stress fractures are a common overuse injury in the pediatric population. Distal fibular and calcaneal stress fractures are considered low-risk stress fractures. Due to their rarity, they have not been studied as thoroughly as other stress fractures. Purpose: To present a descriptive case series of distal fibular and calcaneal stress fractures in the pediatric population and elaborate on demographics, mechanism of injury, management and outcomes. Methods: IRB-approved retrospective study included patients under 18 years at a tertiary children's hospital who were diagnosed with a distal fibular or calcaneal stress fracture/reaction. Demographic data, mechanism of injury, physical exam, radiographic findings, treatment, and outcomes were collected. Descriptive statistical analysis was conducted. Results: 11 patients, 6 distal fibula (4 female, 2 male) and 5 calcaneus (2 female, 3 male) with stress injury on clinical exam and on X-ray or MRI were included. Mean age was 11 years (1-15) and average BMI of 23.5 (16-30.7). The common presenting complaint was pain aggravated by activity that began an average of 3 weeks prior. 7/11 (63.6%) participated in competitive sports: 4/6 with fibular stress fractures were runners (cross country, soccer and sprinting) compared to 0/5 patients with calcaneal involvement. Typical radiographic findings (periosteal reaction, cortical thickening) and a corresponding physical exam was sufficient to diagnose fibular stress fractures in 5/6 patients, with one requiring MRI for definitive diagnosis. 4/5 patients with calcaneal stress fractures required an MRI for a definitive diagnosis, delaying the diagnosis by an average of 3 weeks. 5/6 patients with fibular stress fractures had no other associated pathology, such as additional stress fractures, bone cysts, or osteoid osteomas, whereas 3/5 with calcaneal injuries had at least one of these associated pathologies. Patients with isolated fibular or calcaneal stress fractures (7/11) improved with conservative management, including a controlled ankle motion (CAM) boot, PT, and full activity rest over an average of 6.5 weeks. Out of the remaining 4 patients with associated pathologies, 3/4 improved with conservative management alone after an average of 20 weeks; however, one patient required surgical removal of a bone cyst before complete recovery. Conclusion: A history of pain with significant running, X-ray findings, and physical exam findings were sufficient for diagnosis of fibular stress fractures; however, calcaneal stress fractures were often occult, requiring MRI for definitive diagnosis, and were associated with other pathologies. Conservative management was sufficient for treatment of 91% of patients, regardless of additional fractures or pathology. Fig. 1 Right Ankle X-ray, AP view - Periosteal reaction along the distal right fibular diaphysis, a common finding when stress fractures are found on radiographs. Fig. 2 Left Ankle STIR MRI, sagittal view - Hypointense line through the metaphysis of the calcaneal tuberosity, indicative of a stress fracture. There is surrounding hyperintense marrow edema throughout much of the calcaneus as well.